2013
DOI: 10.1172/jci65167
|View full text |Cite
|
Sign up to set email alerts
|

MFGE8 inhibits inflammasome-induced IL-1β production and limits postischemic cerebral injury

Abstract: Milk fat globule-EGF 8 (MFGE8) plays important, nonredundant roles in several biological processes, including apoptotic cell clearance, angiogenesis, and adaptive immunity. Several recent studies have reported a potential role for MFGE8 in regulation of the innate immune response; however, the precise mechanisms underlying this role are poorly understood. Here, we show that MFGE8 is an endogenous inhibitor of inflammasome-induced IL-1β production. MFGE8 inhibited necrotic cell-induced and ATP-dependent IL-1β p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(101 citation statements)
references
References 28 publications
6
94
1
Order By: Relevance
“…These findings suggest that hypoxia in ischemic areas might be associated with the enhancement of MFG-E8 expression in pericytes/vascular SMCs and ECs. Previous studies have reported that MFG-E8 mRNA and protein expression in organs, including the kidney, liver, and gut, were significantly decreased by I/R Wu et al, 2012;Deroide et al, 2013;Matsuda et al, 2013). Consistent with these previous results, MFG-E8 expression in cutaneous I/R areas was decreased by 0.5-fold at 72 hours after reperfusion.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These findings suggest that hypoxia in ischemic areas might be associated with the enhancement of MFG-E8 expression in pericytes/vascular SMCs and ECs. Previous studies have reported that MFG-E8 mRNA and protein expression in organs, including the kidney, liver, and gut, were significantly decreased by I/R Wu et al, 2012;Deroide et al, 2013;Matsuda et al, 2013). Consistent with these previous results, MFG-E8 expression in cutaneous I/R areas was decreased by 0.5-fold at 72 hours after reperfusion.…”
Section: Discussionsupporting
confidence: 88%
“…Recent studies revealed that MFG-E8 significantly reduces inflammation and protects tissue injury after I/R in several organs including the brain, liver, kidney, and gut Wu et al, 2012;Deroide et al, 2013;Matsuda et al, 2013). These studies demonstrated that MFG-E8 mRNA and protein expression in organs, including kidney, liver, and gut, were significantly decreased by I/R, and that treatment with rMFG-E8 recovered organ dysfunction and suppressed inflammatory responses.…”
Section: Introductionmentioning
confidence: 93%
“…Of note, two studies investigating models of permanent cerebral ischemia have reported protective effects mediated by MFG-E8 through modulation of the inflammatory response. One study reported enhanced IL-1β production and larger infarcts in Mfge8 knockout mice (50), whereas the other correspondingly reported suppression of inflammation after intravenous treatment with recombinant MFG-E8 and reduced infarct size (51). In contrast, we could not detect any significant changes in the inflammatory response after focal cerebral ischemia as measured by the number of activated microglia, as well as the release of inflammatory mediators both in vitro and in vivo (Figs.…”
Section: Discussioncontrasting
confidence: 67%
“…In stroke, the release of DAMPs by the ischemic tissue mediates the activation of PRRs in the CNS. Some of these pathways have been demonstrated to mediate injury following cerebral ischemia Faraco et al, 2007;Qiu et al, 2010 Peroxiredoxins TLR2 and TLR4 Shichita et al, 2012 Heat shock proteins TLR2 and TLR4 Brea et al, 2011 Fibrin/fibrinogen TLR2 and TLR4 Zhang et al, 2012 Extracellular ATP NLRs (P2X7 pathway) Deroide et al, 2013 Histone deacetylase subunit SAP130 CLRs Suzuki et al, 2013 Abbreviations: DAMP, damage-associated molecular pattern; PRR, pattern recognition receptor; HMGB1, high-mobility group box-1; TLR, Toll-like receptor; NLRs, NOD-like receptors; P2X7, purinergic receptor P2X, ligand-gated ion channel 7; CLRs, C-type lectin receptors.…”
Section: The Role Of the Pattern Recognition Receptors On Stroke Pathmentioning
confidence: 99%
“…In agreement with this, recent findings indicate that the milk fat globule-EGF 8 (MFGE8), a secretory glycoprotein that binds to anionic phospholipids, extracellular matrices, and integrins, mediates a neuroprotective effect in brain ischemia by inhibition of the activity of the inflammasome. These effects are attributed to the ability of MFGE8 to limit P2X7 receptor-dependent IL-1β production (Deroide et al, 2013). In this context, direct inhibition of inflammasome activation using antibodies against NRLP1, a member of the NLR family, also induces neuroprotection after stroke (Abulafia et al, 2009).…”
Section: Role Of Nucleotide-binding Oligomerization Domain Receptors mentioning
confidence: 99%